2019
DOI: 10.1111/pace.13721
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of pulmonary vein isolation using second‐generation cryoballoon during atrial fibrillation ablation

Abstract: Background: Currently available second-generation cryoballoon (CB2) is accepted as an effective and safe tool for pulmonary vein isolation (PVI). Although much more data exist about 1-year outcomes of CB2 ablation, data on long-term outcomes are scarce. Objective:We aimed to assess the long-term outcomes of PVI using CB2 in a large-scale symptomatic atrial fibrillation (AF) population at our tertiary referral center. Methods:In this nonrandomized prospective observational study, a total of 486 patients with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
(36 reference statements)
2
24
0
1
Order By: Relevance
“…Vascular complications including groin hematoma, retroperitoneal bleeding, local infection, femoral arterial pseudoaneurysm, or femoral arteriovenous fistula are known as the most common complications of AF catheter ablation with varying incidence rates . Uninterrupted OAC use, full dose periprocedural anticoagulation, the necessity of >1 vascular puncturing with large bore sheaths and center volume have been previously reported as risk factors for access site complications during AF ablation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular complications including groin hematoma, retroperitoneal bleeding, local infection, femoral arterial pseudoaneurysm, or femoral arteriovenous fistula are known as the most common complications of AF catheter ablation with varying incidence rates . Uninterrupted OAC use, full dose periprocedural anticoagulation, the necessity of >1 vascular puncturing with large bore sheaths and center volume have been previously reported as risk factors for access site complications during AF ablation .…”
Section: Discussionmentioning
confidence: 99%
“…Direct OACs were ceased 24‐48 h before the procedure taking the renal function tests into account. The technical details of the second‐generation CB‐based pulmonary vein isolation were defined in detail previously …”
Section: Methodsmentioning
confidence: 99%
“…A growing evidence suggests that second-generation cryoballoon is also safe and effective in patients with persistent AF [29,30]. In persistent AF the isolation of the left atrial appendage as an adjunct to PVI may improve 1-year outcomes compared with the PVI-only strategy using cryoballoon [31].…”
Section: Cryoballoon Ablationmentioning
confidence: 99%
“…A prospective cluster cohort study that involved 4,189 patients showed that the recurrence rate of PeAF did not differ between CBA and RFCA during middle-term follow up [8]. A single-center large-scale study also found that the free survival rate for atrial arrhythmias was 78.6% after a single procedure for PaAF and 72.3% for PeAF at a median 39 months follow-up [9]. CBA treatment also achieved a similar success rate without obvious complications compared to RFCA both in elderly AF patients (>75 years old) and patients with PeAF and longstanding PeAF [10,11].…”
Section: Introductionmentioning
confidence: 96%